Penerapan Metode Hill Climbing Pada Sistem Informasi Geografis Untuk Mencari Lintasan Terpendek - Dangkua, Eka Vickraien; Gunawan, Vincencius; Adi, Kusworo (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
Heuristic search methods is one of the methods commonly in use in finding the shortest path, one of which, namely the methods Hill Climbing process where testing is done using heuristic functions. Problems generally encountered is the shortest path search to solve the problem of distance can be changed into a graph structure, where the point of declaring the city and the State line that connects the two cities. From the logic so that it can locate destinations and save on travel costs. The hallmarks of this algorithm are all possible solutions will have then checked one by one from the left side, so it will be obtained solutions with optimal results. On a Hill Climbing method according to case using geographic information systems as a tool in making a decision, by way of collect, examine, and analyze information related to digital map. with a combination of Hill Climbing method and geographic information systems can result in an application that is certainly feasible for use in the search path problems. Â  Keywords: Hill Climbin method; digital map; Geographic Information Systems